Adult Reading: Prestige or Value - Javrh, Petra (Bralni vzori 2, 2025)
In the world of digital information, reading as the decoding of messages is one of the fundamental skills that should be mastered as effectively as possible. This paper discusses the encouragement of reading from the perspective of adult education. We analyzed how reading-related support and incentives are integrated into the curricula of officially recognized programs in adult education. The analysis was based on the assumption that such programs include the development of reading skills in their curricula, as required by the Guidance for the Preparation of Adult Education Programs. We emphasize the importance of considering adults diverse life experiences, which shape the specific nature of reading support for adult learners. Supporting the development of reading skills is a professionally demanding task in the context of non-formal adult education. It is essential to take into account the key characteristics that adult learners bring to the learning process. These are particularly related to their autonomy in deciding to engage in non-formal education, their diverse life experiences, and the influence of personal beliefs and complex contextual factors.